2018
DOI: 10.4025/revcivet.v5i1.39577
|View full text |Cite
|
Sign up to set email alerts
|

Parasitos com potencial zoonótico em fezes de cães presentes na areia da praia do Laranjal, Pelotas-RS

Abstract: O objetivo deste estudo, foi analisar a contaminação das fezes de cães, presentes na areia da praia do laranjal, na cidade de Pelotas, estado do Rio Grande do Sul, por helmintos gastrintestinais de cães, principalmente os com potencial zoonótico, como Ancylostoma spp. e Toxocara spp. Foram coletadas e analisadas 139 amostras de fezes de cães, as quais, 84 foram positivas para pelo menos um tipo de helminto gastrintestinal, representando 60,4% e 11% das amostras apresentavam associação de parasitas. O gênero, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
2
3
1
Order By: Relevance
“…Amongst 180 analyzed dog feces samples, 65,55% (118) had parasites. Such a result resembles those found by Ferraz et al (2018), who obtained 60,4% of samples with parasites (139) collected in Laranjal beach, in Pelotas (RS, Brazil). The most found parasitic genre by the author was Ancylostoma spp., observed in 77 samples.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Amongst 180 analyzed dog feces samples, 65,55% (118) had parasites. Such a result resembles those found by Ferraz et al (2018), who obtained 60,4% of samples with parasites (139) collected in Laranjal beach, in Pelotas (RS, Brazil). The most found parasitic genre by the author was Ancylostoma spp., observed in 77 samples.…”
Section: Resultssupporting
confidence: 89%
“…The prevalence of parasites with zoonotic potential found in sand samples indicates that both humans and animals are in jeopardy concerning their health, once they are susceptible to accidental ingestion of eggs or percutaneous penetration of parasites' larvae since these places are designated for leisure activities, especially used by kids, who are used to touching the mouth with their hands after contacting contaminated soil (FERRAZ et al, 2018, OLIVEIRA, 2018.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study in the 2016/2017 summer season on the beaches of southern Florianópolis, SC, showed even higher occurrence of parasites from dogs and cats, where Campeche Beach presented 72.22% of fecal samples contaminated with hookworm predominance (Bricarello et al, 2018). The occurrence of this helminth was predominant at the Morro das Pedras, Campeche and Pinheira beaches, the same way it was observed in other studies carried out on beaches in Brazil (Blazius et al, 2005;Coronato et al, 2012;Ferraz et al, 2018;Pedrosa et al, 2014;Santos et al, 2006).…”
Section: Discussionsupporting
confidence: 59%
“…When analyzing studies that apply experimental designs, similar to the present study, it was verified that there is still no standardization as to the lowest experimental n capable of representing, in a sensitive way, the risk estimates related to infection of the zoonoses of interest. Studies were carried out with experimental n ranging from 18 up to 137 for each studied geographic location (Bricarello et al, 2018;Ferraz et al, 2018Ferraz et al, , 2019Santarém et al, 2012). Considering these pieces of information, the present research was carried out with 150 fecal samples representing Pinheira Beach and 149 fecal samples representing the beaches Morro das Pedras and Campeche.…”
Section: Study Trial and Statistical Analysismentioning
confidence: 99%